Australian perspective on engaging with South Korea in the Indo‐Pacific. Issue 1 (13th January 2023) - Kim, Jiye; Raswant, Arpit
Abstract: How do the US allies engage with other actors in the US‐led Indo‐Pacific security order? This article examines this question in the case of Australia. We argue that the regional strategic network is a key consideration for Australia to facilitate its interaction with a target country in the Indo‐Pacific. This article analyzes Australia's approach toward South Korea as an example demonstrating the significance of the regional strategic network in shaping Australia's diplomacy. It does so by addressing the following three questions. First, what is Australia's vision for the Indo‐Pacific? Second, how does Australia perceive South Korea's role in the Indo‐Pacific? Third, how does Australia's Indo‐Pacific vision find the relevance of South Korea for Australia's security interests? The article elucidates that Australia's view on South Korea's place in the Indo‐Pacific security network influences Australia's interaction with South Korea and consequently plays an integral part in the US‐led regional security order‐building process. 摘要: 美国盟友如何在美国主导的印太安全秩序中与其他行动者接触？本文以澳大利亚为例，对该问题进行分析。我们论证认为，区域战略网络是澳大利亚促进其与印太地区目标国家互动的关键考量因素。本文以澳大利亚对韩国的接触方式为例进行分析，证明了区域战略网络在影响澳大利亚外交方面的重要性。为此，本文分析了以下三个问题。第一，澳大利亚对印太地区的愿景是什么？第二，澳大利亚如何看待韩国在印太地区的作用？第三，澳大利亚的印太愿景如何发现韩国与澳大利亚安全利益的相关性？本文阐明，澳大利亚对"韩国在印太安全网络中的地位"的看法会影响澳大利亚与韩国的互动，进而在美国主导的区域安全秩序建立过程中发挥不可或缺的作用 Resumen: ¿Cómo interactúan los aliados de EE. UU. con otros actores en el orden de seguridad del Indo‐Pacífico liderado por EE. UU.? Este artículo examina esta cuestión en el caso de Australia. Argumentamos que la red estratégica regional es una consideración clave para que Australia facilite su interacción con un país objetivo en el Indo‐Pacífico. Este artículo analiza el enfoque de Australia hacia Corea del Sur como un ejemplo que demuestra la importancia de la red estratégica regional en la configuración de la diplomacia de Australia. Lo hace abordando las siguientes tres preguntas. Primero, ¿cuál es la visión de Australia para el Indo‐Pacífico? En segundo lugar, ¿cómo percibe Australia el papel de Corea del Sur en el Indo‐Pacífico? Tercero, ¿cómo encuentra la visión del Indo‐Pacífico de Australia la relevancia de Corea del Sur para los intereses de seguridad de Australia? El artículo aclara que la opinión de Australia sobre el lugar de Corea del Sur en la red de seguridad del Indo‐Pacífico influye en la interacción de Australia con Corea del Sur y, en consecuencia, juega un papel integral en el proceso de construcción del orden de seguridad regional liderado por Estados Unidos.